Blockade of CD40–CD154 pathway interactions suppresses ectopic lymphoid structures and inhibits pathology in the NOD/ShiLtJ mouse model of Sjögren's syndrome. Issue 7 (22nd July 2019) - Wieczorek, Grazyna; Bigaud, Marc; Pfister, Sabina; Ceci, Melanie; McMichael, Katriona; Afatsawo, Catherine; Hamburger, Meike; Texier, Celine; Henry, Maurane; Cojean, Celine; Erard, Marinette; Mamber, Nadja; et al.
Abstract : Objective: To examine the role of CD40–CD154 costimulation and effects of therapeutic pathway blockade in the non-obese diabetic (NOD/ShiLtJ) model of Sjögren's syndrome (SS). Methods: We assessed leucocyte infiltration in salivary glands (SGs) from NOD/ShiLtJ mice by immunohistochemistry and examined transcriptomics data of SG tissue from these animals for evidence of a CD40 pathway gene signature. Additionally, we dosed MR1 (anti-CD154 antibody) in NOD mice after the onset of SS-like disease and examined the effects of MR1 treatment on sialadenitis, autoantibody production, SG leucocyte infiltration, gene expression downstream of CD40 and acquaporin 5 (AQP5) expression. Results: We could detect evidence of CD40 expression and pathway activation in SG tissue from NOD mice. Additionally, therapeutic treatment with MR1 suppressed CD40 pathway genes and sialadenitis, inhibited ectopic lymphoid structure formation and autoantibody production, as well as decreased the frequency of antibody-secreting cells in SGs but had minimal effects on AQP5 expression in NOD/ShiLtJ SGs. Conclusion: CD40–CD154 interactions play an important role in key pathological processes in a mouse model of SS, suggesting that blockade of this costimulatory pathway in the clinic may have beneficial therapeutic effects in patients suffering from this autoimmune exocrinopathy.